High-speed technology trading innovations and capital market performance in Bulgaria - Julia Stefanova (Financial Studies, 2018)
The paper analyses the effects of technology-based innovative techniques on Bulgarian capital market -algorithmic trading, in general, and high frequency trading (HFT), in particular - from macroeconomic costs-benefits perspective. Overwhelmingly, empirical studies emphasize that HFT improves the quality of financial markets in terms of increased liquidity, lowered transaction costs and fast price discovery. On the other side, HFT can have potential destabilizing effects, especially on emerging markets, which require increased regulation. Against this background, the European Union (EU) has introduced new regulatory measures targeting HFT, in 2018, which require fast adaptation of all market participants. Empirically, the author argues that there is a relationship between HFT, increased market volatility, fall in trading activity, liquidity and market capitalization on the Bulgarian capital market following the global financial crisis, concluding that the reasons for the fall in capital market activity are not only purely economic. Last, it elaborates on prospective implications for the Bulgarian capital market after the implementation of the new EU regulation targeting HFT.
Keywords: G12; G19; G23; 330; algorithmic trading; liquidity; volatility; market capitalization; systemic risk; EU integration